Pengaruh Pelatihan, Motivasi, dan Lingkungan Kerja Terhadap Produktivitas Kerja (Studi Kasus pada Karyawan Bagian Body & Rangka CV. Laksana) - PR, Aditya Yoga; Hadi, Sudharto Prawata (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2018)
Labor productivity is the ability to perform their activities to achieve the output with defined target, but often there are obstacle in fullfilling the target.Â To achieve the target CV. Laksana must take into account many factors which influence the labor productivity.Â This purpose of this study is to identify the effect of training, motivation, and work environment to labor productivity CV. Laksana Frame and Body Division. This type of research is explanatory research. The sample used is 118 respondents. The sampling techniques is probability sampling. The data collection techniques are questionnaire, observation and literature review. Data analysis techniques are, validation, realibility, correlation, simple linear regression, multiple linear regression, t and f test with IBM SPSS (Statistical Product and Service Solutions) program version 21.0. Based on the analysis, it can be concluded that training, motiviation, and work environment affects labor productivity through testing simple linear regression produce regression value of 0.467, 0.402, and 0.479. The adviceÂ proposed to the company are to improve the suitability of training materials to work needs, the accuracy of training methods, rewards of outstanding employees, workplace layouts, and workplace safety.